Outcomes of symptomatic abdominal aortic aneurysm repair - De Martino, Randall R. (J Vasc Surg, 2010)
OBJECTIVE: Operative mortality of patients undergoing symptomatic abdominal aortic aneurysm (Sx-AAA) repair has been reported at 6% to 30% during the past 25 years. We used a multicenter regional database to describe the contemporary outcomes of patients undergoing repair of Sx-AAA. METHODS: All patients undergoing infrarenal AAA repair in 11 hospitals comprising the Vascular Study Group of Northern New England (VSGNNE) between 2003 and 2009 were studied. Sx-AAA was prospectively defined as an AAA accompanied by abdominal or back pain or tenderness, but without rupture. The primary study end point was in-hospital mortality. Secondary end points included in-hospital postoperative major adverse events (MAE) and late survival. These outcomes were compared between symptomatic patients and contemporary VSGNNE cohorts of elective (E-AAA) and ruptured AAAs (R-AAAs) treated within the same study period. RESULTS: During the study period, 2386 AAA repairs were performed, comprising 1959 (82%) E-AAAs, 156 (7%) Sx-AAAs, and 271 (11%) R-AAAs. Repair was endovascular in 945 (48%) E-AAAs, 60 (38%) Sx-AAAs, and 33 (12%) R-AAAs. Hospital mortality was 1.7% for E-AAA repair and 1.3% for Sx-AAA repair, but was 34.7% for R-AAA repair (P < .001). The MAE rates were 20%, 35%, and 63%, respectively, for E-AAA, Sx-AAA, and R-AAA repairs (P < .001). The mean Glasgow Aneurysm Score (GAS) for Sx-AAA patients who survived was 79 ± 12. Those who died had an average score of 92 ± 7, and 83% of all Sx-AAA and R-AAA patients who died had a GAS >85. Kaplan-Meier analysis demonstrated that at 1 and 4 years, Sx-AAA repair was associated with intermediate survival (83% and 68%) compared with E-AAA repair (89% and 73%) and R-AAA repair (49% and 35%; P < .001). CONCLUSION: The operative mortality of patients with Sx-AAA in contemporary practice appears better than that previously reported in the literature. Despite low operative mortality, MAE and late survival are intermediate compared with E-AAA and R-AAA repair. Review of previous series shows a trend for lower operative mortality after Sx-AAA repair in more recent series, which likely reflects improved perioperative care and more use of endovascular aneurysm repair.